Efferocytosis and Its Role in Inflammatory Disorders - Ge, Yun; Huang, Man; Yao, Yong-ming (Frontiers in Cell and Developmental Biology, 2022)
Efferocytosis is the effective clearance of apoptotic cells by professional and non-professional phagocytes. The process is mechanically different from other forms of phagocytosis and involves the localization, binding, internalization, and degradation of apoptotic cells. Defective efferocytosis has been demonstrated to associate with the pathogenesis of various inflammatory disorders. In the current review, we summarize recent findings with regard to efferocytosis networks and discuss the relationship between efferocytosis and different immune cell populations, as well as describe how efferocytosis helps resolve inflammatory response and modulate immune balance. Our knowledge so far about efferocytosis suggests that it may be a useful target in the treatment of numerous inflammatory diseases.